TEOLOGI LINGKUNGAN HIDUP DALAM PERSPEKTIF ISLAM - Fata, Ahmad Khoirul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
The damage of nature is believed to be derived from the man, the human mindset who place themselves at the center of this life (anthropocentrism). In this context the teachings of the monotheistic religions are often accused of having a major contribution to the establishment of the doctrine of anthropocentrism paradigm of human superiority over nature. This paper attempts to trace